The crosstalk between senescence, tumor, and immunity: molecular mechanism and therapeutic opportunities - Zehua Wang; Chen Chen; Jiaoyu Ai; Yaping Gao; Lei Wang; Shurui Xia; Yongxu Jia; Yanru Qin (MedComm)
Abstract Cellular senescence is characterized by a stable cell cycle arrest and a hypersecretory, proinflammatory phenotype in response to various stress stimuli. Traditionally, this state has been viewed as a tumor‐suppressing mechanism that prevents the proliferation of damaged cells while activating the immune response for their clearance. However, senescence is increasingly recognized as a contributing factor to tumor progression. This dual role necessitates a careful evaluation of the beneficial and detrimental aspects of senescence within the tumor microenvironment (TME). Specifically, senescent cells display a unique senescence‐associated secretory phenotype that releases a diverse array of soluble factors affecting the TME. Furthermore, the impact of senescence on tumor–immune interaction is complex and often underappreciated. Senescent immune cells create an immunosuppressive TME favoring tumor progression. In contrast, senescent tumor cells could promote a transition from immune evasion to clearance. Given these intricate dynamics, therapies targeting senescence hold promise for advancing antitumor strategies. This review aims to summarize the dual effects of senescence on tumor progression, explore its influence on tumor–immune interactions, and discuss potential therapeutic strategies, alongside challenges and future directions. Understanding how senescence regulates antitumor immunity, along with new therapeutic interventions, is essential for managing tumor cell senescence and remodeling the immune microenvironment.